2022
DOI: 10.3389/fpsyt.2022.826043
|View full text |Cite|
|
Sign up to set email alerts
|

Abilities and Disabilities—Applying Machine Learning to Disentangle the Role of Intelligence in Diagnosing Autism Spectrum Disorders

Abstract: ObjectiveAlthough autism spectrum disorder (ASD) is a relatively common, well-known but heterogeneous neuropsychiatric disorder, specific knowledge about characteristics of this heterogeneity is scarce. There is consensus that IQ contributes to this heterogeneity as well as complicates diagnostics and treatment planning. In this study, we assessed the accuracy of the Autism Diagnostic Observation Schedule (ADOS/2) in the whole and IQ-defined subsamples, and analyzed if the ADOS/2 accuracy may be increased by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Currently, much of the past research on diagnostic models has focused on diagnostic imaging, neglecting the importance of demographic and behavioral observational data ( 40 ). Meanwhile, fewer studies have focused on early diagnosis and screening of ASD combined with ID ( 41 , 42 ). Furthermore, in the context of healthcare resource shortages and COVID-19 pandemic, the application of simple and effective diagnostic tools geared toward most primary care physicians can greatly reduce the burden on the healthcare system.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, much of the past research on diagnostic models has focused on diagnostic imaging, neglecting the importance of demographic and behavioral observational data ( 40 ). Meanwhile, fewer studies have focused on early diagnosis and screening of ASD combined with ID ( 41 , 42 ). Furthermore, in the context of healthcare resource shortages and COVID-19 pandemic, the application of simple and effective diagnostic tools geared toward most primary care physicians can greatly reduce the burden on the healthcare system.…”
Section: Introductionmentioning
confidence: 99%
“…The last ML model attempted at performing a differential diagnosis between PDD and MSDD. This approach, making use of ML for purposes of differential diagnosis based on best-practice diagnostic instruments for autism, was already proposed with satisfying results, even though it was limited to a lower number of models from the ML perspective [ 39 ], focused on some specific clinical variables [ 40 ] or both [ 41 ]. In this respect, our work comparing different classification models showed that to the benefit of the clinician, the age at diagnosis and birth weight were seen to be the variables, which were the most predictive for distinguishing the two disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Based on a previous finding, we further think that the influence of intelligence on existing and well established ASD diagnostic tools should be considered more explicitly. In this vein, we observed recently, that with respect to the cut-off exceedance of the Autism Diagnostic Observation Schedule-2 [ADOS-2 ( 41 )], individuals with below average IQ are significantly over classified (=false positives), while individuals with above average IQ are significantly under classified or misclassified (=false negatives) in regard to an ASD diagnosis [Wolff et al ( 42 )]. The misclassification of individuals with above average IQ leads to further questions.…”
Section: Difficulties In Terms Of Validity: Iq Measurement Autism Spe...mentioning
confidence: 99%